Research on Gender and Sexualities in Africa - Bennett, Jane; Tamale, Sylvia (Oxford CODESRIA (Conseil pour le Developpement de la Recherche Economique et Sociale en Afrique), 2017)
Cover -- Title page -- Copyright page -- Contents -- Preface -- Contributors -- 1. 'Fashionable Strategies': Travels in Gender and Sexuality Studies -- Sexualities Research 'in the West'? -- Contemporary Writing on Gender and Sexualities Within African Contexts -- Bringing it Home -- Conclusion -- Notes -- References -- 2. Exploring the Contours of African Sexualities: Religion, Law and Power -- Introduction: Linking Religion, Culture, Law and Sexuality -- Law, Culture and Religion Viewed through the Lens of Power -- The Sexual Citizen: Between Desire and the Law -- Out of the Margins: Challenging Structures of Sexual Oppression -- Conclusion: African Religion and Sexualities - Toward a Sociolegal Reconstruction -- Notes -- 3. The Power of Pleasure: Re-conceptualising Sexualities -- Framing Alternative Approaches to Analysis of Female Sexualities -- Epistemic Ruptures in Thinking about Gender -- Female Initiation Rituals in Northern Mozambique -- Preparations of the Erotic Body -- Body Tattoos/Scarifications -- Hip Belts of Glass Beads - Missangas -- Elongated Labia -- Labia Elongation, Sexual Self-confidence and Categorisations -- Erotic Movements -- Conclusion -- Notes -- References -- 4. Rethinking Sex and Secrecy in Precolonial African History: A Focus on Kenya -- Introduction -- Theorising Sex and Secrecy -- Kenya and 'Sexuality' under Colonial Anthropology -- Conclusion -- References -- 5. The 'G-String' as a Space for Sexual and Political Imagination: Rethinking Discourses of Youth, Power and Globalisation in Kenya -- Introduction -- The Voice of the 'G-String' as 'African Clothing' -- Notes -- References -- 6. 'Daddy, Today we have a Match! 'Women's Agentic Strategies in Initiating Sexual Intercourse in an Urban Ghanaian Community -- Introduction -- Methodology -- Data Analysis -- Results -- Discussion -- References
7. Construction of Social Identity in the Erotic Juju Song-poetry of Saint Janet -- Introduction -- Reflections on Erotic Music -- Strategies of Representation of Identity and Sexual Diversity -- Agency and the Contradiction of the Yoruba Society -- Conclusion -- References -- Nigerian Newspapers -- 8. Language, Sex and Power Relations: An Analysis of Shona Sexual Expressions -- Introduction -- Approach to the Study -- Uncovering the Connections between Shona Language -- Bibliography -- 9. Feminism: How Women in Uganda are Shaping the Way we Think about Sex and Politics -- Introduction -- Framing the Debate -- Research Methods -- Women, Sex and Politics in Uganda -- Emplacing Trends in Historical Perspective -- Feminist Achievements into the Late 2000s -- The Contemporary Spectrum - Resistance and Resignation -- What the Women Say -- Conclusion -- References -- 10. HIV-Positive Women 'Virgins': The Complexities of Discourse on Issues of Sex and Sexuality in Zimbabwe -- Introduction -- HIV-Positive Women Virgins and the Discourse of 'Othering' -- Discourses on Sex and Sexuality in Zimbabwe: The Challenges -- HIV-Positive Virgins, Sex and Sexuality: The Dilemma -- Experiences, Dreams and Fears of the HIV-Positive Virgins -- Conclusion -- References -- 11. Sexual Health Promotion in Tanzania: Narratives on Young People's Intimate Relationships -- Introduction: The Sexual 'Behaviour' of Youths -- Sexual Behaviour Change and Health Promotion Approaches -- Sexual Behaviour Change and Health Promotion in the 'Developing' World: The ABC Approach -- Research Methods for Studying Sexual 'Behaviour' -- The Narrative Study of Sexual 'Behaviour' -- Methodological and Contextual Issues -- Conclusions and Ways Forward -- Acknowledgements -- References -- Index -- Back cover
Keywords: Gender identity--Africa; Electronic books